Strategies for screening cord blood for a public cord blood bank in high HIV prevalence regions. (15th May 2018) - Meissner-Roloff, M.; Gaggia, L.; Vermeulen, M.; Mazanderani, A. F. H.; du Plessis, N. M.; Steel, H. C.; Pepper, M. S.
Abstract : The probability of a Black African finding a matched unrelated donor for a hematopoietic stem cell transplant is minimal due to the high degree of genetic diversity amongst individuals of African origin. This problem could be resolved in part by the establishment of a public cord blood (CB) stem cell bank. The high prevalence of human immunodeficiency virus (HIV) amongst women attending antenatal clinics in sub-Saharan Africa together with the risk of mother-to-child transmission increases the risk of transplant transmissible infection. In addition to screening the mother in a period inclusive of 7 days prior to the following delivery, we propose that all CB units considered for storage undergo rigorous and reliable screening for HIV. The Ultrio-plus ® assay is a highly specific and sensitive test for detecting HIV, hepatitis-B and hepatitis-C viruses in peripheral blood. We validated the Ultrio-plus ® assay for analytical sensitivity in detecting HIV in CB at the level of detection of the assay. Until more comprehensive and sensitive methods are developed, the sensitivity and reliability of the Ultrio-plus ® assay suggest that it could be used for the routine screening of CB units in conjunction with currently recommended maternal screening to reduce the risk of transplant transmissible infection.